Type 2 diabetes complications are associated with liver fibrosis independent of hemoglobin A1c - Hirsh D. Trivedi; Qua Tran; Zachary Fricker; Michael P. Curry; Jonathan X. Li; Michelle Lai (Annals of Hepatology, 2023)
Introduction and Objectives: The association between type 2 diabetes, non-alcoholic fatty liver disease, and liver fibrosis is well established, but it is unknown whether complications of type 2 diabetes influence fibrosis levels. We defined the complications of type 2 diabetes by the presence of diabetic nephropathy, retinopathy, or neuropathy and aimed to evaluate their association with the degree of liver fibrosis measured by the fibrosis-4 (FIB-4) index. Materials and Methods: This is a cross-sectional study evaluating the association of type 2 diabetes complications with liver fibrosis. A total of 2389 participants were evaluated from a primary care practice. FIB-4 was evaluated as a continuous and categorical measure using linear and ordinal logistic regression. Results: Patients with complications were older, had higher hemoglobin A1c, and a higher median FIB-4 score (1.34 vs. 1.12, P<0.001). On adjusted analysis, type 2 diabetes complications were associated with higher fibrosis by continuous FIB-4 score (Beta-coefficient: 0.23, 95% confidence interval [CI]: 0.004-1.65) and demonstrated increased odds of fibrosis by categorical FIB-4 score (odds ratio [OR]: 4.48, 95% CI: 1.7-11.8, P=0.003), independent of hemoglobin A1c level. Conclusions: The presence of type 2 diabetes complications is associated with the degree of liver fibrosis, independent of hemoglobin A1c level.